Removal of Etalon Features in the Far-Infrared–Terahertz Transmittance Spectra of Thin Polymer Films. Issue 12 (December 2020) - Schade, Ulrich; Cao, Dawei; Puskar, Ljiljana; Ritter, Eglof; Beckmann, Jörg
Etalon features in infrared spectra of stratified samples, their influence on the interpretation, and methods to circumvent their presence in infrared spectra have been in discussion for decades. This paper focuses on the application of a method originally developed to remove interference fringes in the mid-infrared spectra for far-infrared Fourier transform spectroscopy on thin polymer films. We show that the total transmittance reflectance technique, commonly used for mid-infrared, also works successfully in the far-infrared spectral range where other approaches fail. Experimental spectra obtained by such technique are supported by model calculations and reveal the possibility and limits to obtain almost undisturbed far-infrared spectra which are suitable to determine low-energy vibrations of ionomer salts under certain sample conditions.